(untitled) - Rigg, Jonathan (London, 1997)
This book charts the development of Southeast Asia, examining the economies of Vietnam, Laos, Cambodia and Burma alongside the established Asian market economies. Drawing on case studies from across the region, the author assesses poverty and ways in which the poor are identified and viewed. Process and change in the rural and urban 'worlds' are examined in detail, focusing on the strengthening rural-urban interaction as 'farmers' make a living in the urban-industrial sector and factories relocate into agricultural areas.
Keywords: Southeast Asia,Human geography,Đông Nam Á,Địa lý nhân văn; Geography,Địa lý; Southeast Asia,Đông Nam Á